A multifunctional gallium-mof/hydrogel construct based on tetratopic ligands and pectin: structural optimization and biomedical potential - Ali, Fattma A.; Faez Sead, Fadhil; Altalbawy, Farag M. A.; Yousif Jamil, Nawfal; Salih Sahib, Ahmed; Saad Abdulali, Zahraa; Alwan, Mariem; Jawad, Mahmood; Mushtaq, Hiba; Smerat, Aseel; Muzammil, Khursheed (Frontiers in Materials, 2025)
A novel hydrogel-based material was synthesized using gallium nitrate, a tetratopic pyridine-carboxylate ligand (H4TBAPy), oxidized pectin, and chitosan (Gallium-MOF/Hydrogel). This composite material incorporates a metal–organic framework (MOF) network within a biopolymeric hydrogel matrix. The structure was characterized via scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, carbon/hydrogen/nitrogen/oxygen elemental analysis (CHNO EA), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), energy-dispersive X-ray (EDX) and EDX mapping, confirming the formation of a nanoscale MOF-hydrogel system with high surface area and uniform morphology. The antimicrobial activity of the material was evaluated against clinically relevant fungal species and Gram-positive and Gram-negative bacterial strains, showing superior minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and minimum bactericidal concentration (MBC) values compared to two standard antibiotics. Furthermore, cytotoxicity assays on against skin (A-431), breast (MCF-7), and bone cancer (MG-63) cancer cells revealed strong anticancer effects, likely due to the bioactive nature of the Ga-MOF core and synergistic interactions with pectin and chitosan. The obtained results highlight the potential of this Ga-based hydrogel as a multifunctional platform for biomedical applications.